2011
DOI: 10.4049/jimmunol.1004231
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic HIV-1 Gag Antigens Can Be Processed and Presented to Human HIV-Specific CD8+ T Cells

Abstract: Polyvalent “mosaic” HIV immunogens offer a potential solution for generating vaccines that can elicit immune responses against genetically diverse viruses. However, it is unclear whether key T cell epitopes can be processed and presented from these synthetic antigens and recognized by epitope-specific human T cells. Here we tested the ability of mosaic HIV immunogens expressed by recombinant, replication-incompetent adenovirus serotype 26 vectors to process and present major HIV clade B and clade C CD8 T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…PBMC were first stained with the blue viability dye (Molecular Probes, Invitrogen) for 15 min, followed by tetramer staining for 30 min at room temperature. Cells were then surface stained with the following human antibody panel: CD3, CD8, CD4, CD14, CD19, and CD56 (BD Pharmingen) (37). Samples were acquired on the BD LSRFortessa (BD Biosciences), and data analysis was performed using FlowJo version 9.0.2.…”
Section: Methodsmentioning
confidence: 99%
“…PBMC were first stained with the blue viability dye (Molecular Probes, Invitrogen) for 15 min, followed by tetramer staining for 30 min at room temperature. Cells were then surface stained with the following human antibody panel: CD3, CD8, CD4, CD14, CD19, and CD56 (BD Pharmingen) (37). Samples were acquired on the BD LSRFortessa (BD Biosciences), and data analysis was performed using FlowJo version 9.0.2.…”
Section: Methodsmentioning
confidence: 99%
“…A pair of mosaic antigens used in combination elicited more potent and cross-reactive responses than a nonmosaic pair of immunogens that represented a B and C clade combination (26). Furthermore, Ndhlovu et al demonstrated that mosaic HIV antigens expressed by rAd26 are processed into natural epitopes that are recognized by human HIV-specific CD8 ϩ T lymphocytes (28). In a rhesus monkey vaccine study, we demonstrated that an increase from 2-valent to 3-valent mosaic Envs enhanced the breadth and potency of T cell and antibody responses against natural variants (29).…”
mentioning
confidence: 99%
“…An alternative strategy to contend with global HIV-1 diversity is to use polyvalent full-length mosaic immunogens (4,10) that are designed to maximize immunologic coverage of HIV-1 sequence diversity while maintaining conserved sequences in their natural context (4,18). These full-length mosaic immunogens have been shown to induce an increased breadth and depth of HIV-1-specific cellular immune responses compared to those of natural and consensus HIV-1 antigens in rhesus monkeys (3,24).…”
mentioning
confidence: 99%